The presence of Argentinian Composers in the Latin American Courses for Contemporary Music. (Revista Argentina de Musicología, 2014)
Created by a team of composers as a continental itinerant link and self-managed with no institutional obligations, the Cursos Latinoamericanos de Música Contemporánea became a forum of reflection and discussion within a flexible and interdisciplinary structure. This text covers the presence and active participation as teachers of various outstanding Argentinian composers, their works and pedagogic proposals along the fifteen editions of these courses carried out between 1971 and 1989. Also included are brief references to other participants from Argentina (performers, pedagogues and individuals from other artistic and cultural areas).
Keywords: CLAEM; Bazán; Bértola; Etkin; Gandini